lo g 3 4 × lo g 4 5 × lo g 5 6 × lo g 6 7 × lo g 7 8 × lo g 8 9 = ?
This problem is a part of this set .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great explanation ! :D
Using the base changing rule (here I will use natural logarithm as the new base), we will get that l o g a b = l n ( a ) l n ( b ) With this it is possible to see that the remaining terms will be l n ( 3 ) l n ( 9 ) = l n ( 3 ) 2 l n ( 3 ) = 2
Problem Loading...
Note Loading...
Set Loading...
We'll convert to a base of 3 since that's the first base used in the question.
lo g 3 4 ⋅ lo g 3 4 lo g 3 5 ⋅ lo g 3 5 lo g 3 6 ⋅ lo g 3 6 lo g 3 7 ⋅ lo g 3 7 lo g 3 8 ⋅ lo g 3 8 lo g 3 9 = ?
lo g 3 9 = ?
lo g 3 3 2 = ?
2 lo g 3 3 = ?
2 ⋅ 1 = ?
? = 2
The answer is 2